2022
DOI: 10.2174/1570163818666210203181542
|View full text |Cite
|
Sign up to set email alerts
|

Prunella vulgaris L: Critical Pharmacological, Expository Traditional Uses and Extensive Phytochemistry: A Review

Abstract: Background: Prunella vulgaris, family Lamiaceae also known as self-heal, has been traditionally used as an expectorant, anti-inflammatory, anti-pyretic, and anti-rheumatic. Due to widespread distribution of the plant, Vulgaris is also called ‘vulgar’ in Latin adjective meaning common. Objective: The objective of this review was to describe the relevant aspects of phytochemistry and therapeutic uses of different fractions as well as isolated compounds from Prunella vulgaris. An attempt was also made to enume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…1 "Secrets of Green Bag" (Qíng Náng Mì Jué, 青 囊 秘 诀; Ming Dynasty, AD 1368-1644) and many other Chinese herbal works have recorded similar efficacy as mentioned above. 2 In our previous scientific study on screening antiviral active components from medicinal herbs, we found that PVE30, the water-extracting ethanol-precipitating extract prepared from PS, had significant anti-herpes simplex virus (HSV) [including type I (HSV-1, infect labia oris) and type II (HSV-2, infect genitals)] activity in vitro 3,4 ; the results were consistent with the recorded efficacy in ancient works. The EC 50 values (μg/mL ± SD) of PVE30 against acyclovir (ACV)-sensitive HSV-1/KOS and HSV-2/G strains were 45.62 ± 3.37 and 57.14 ± 2.37, respectively, and those against ACVresistant HSV-1/Blue, HSV-1/106, and HSV-1/153 strains were 54.54 ± 2.05, 53.86 ± 4.66, and 39.39 ± 0.63 respectively.…”
Section: Introductionsupporting
confidence: 62%
“…1 "Secrets of Green Bag" (Qíng Náng Mì Jué, 青 囊 秘 诀; Ming Dynasty, AD 1368-1644) and many other Chinese herbal works have recorded similar efficacy as mentioned above. 2 In our previous scientific study on screening antiviral active components from medicinal herbs, we found that PVE30, the water-extracting ethanol-precipitating extract prepared from PS, had significant anti-herpes simplex virus (HSV) [including type I (HSV-1, infect labia oris) and type II (HSV-2, infect genitals)] activity in vitro 3,4 ; the results were consistent with the recorded efficacy in ancient works. The EC 50 values (μg/mL ± SD) of PVE30 against acyclovir (ACV)-sensitive HSV-1/KOS and HSV-2/G strains were 45.62 ± 3.37 and 57.14 ± 2.37, respectively, and those against ACVresistant HSV-1/Blue, HSV-1/106, and HSV-1/153 strains were 54.54 ± 2.05, 53.86 ± 4.66, and 39.39 ± 0.63 respectively.…”
Section: Introductionsupporting
confidence: 62%
“…[9][10][11][12] PV mainly contains terpenoids, phenolic acids, organic acids, sterols, coumarins, flavonoids, polysaccharides, and volatile oils. [10] Modern pharmacological studies have shown that its extracts have a variety of biological activities, such as antioxidation, regulating immune function, anti-inflammatory, antibacterial, antiviral, and regulating the microenvironment of tumor metastasis. [10,11] With the extensive clinical application of PV, the experimental research of PV has gradually deepened, and its pharmacological effects and molecular mechanism of action are gradually clear.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Therefore, PV is also commonly used in clinical treatment of thyroid cancer, breast cancer, liver injury, hypertension, hyperglycemia, prostate diseases, and other diseases. [9][10][11][12] PV mainly contains terpenoids, phenolic acids, organic acids, sterols, coumarins, flavonoids, polysaccharides, and volatile oils. [10] Modern pharmacological studies have shown that its extracts have a variety of biological activities, such as antioxidation, regulating immune function, anti-inflammatory, antibacterial, antiviral, and regulating the microenvironment of tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations